2021
DOI: 10.1055/s-0041-1731761
|View full text |Cite
|
Sign up to set email alerts
|

No Microscope? No Problem: A Systematic Review of Microscope-Free Microsurgery Training Models

Abstract: Background Benchtop microsurgical training models that use digital tools (smartphones, tablets, and virtual reality [VR]) for magnification are allowing trainees to practice without operating microscopes. This systematic review identifies existing microscope-free training models, compares models in their ability to enhance microsurgical skills, and presents a step-by-step protocol for surgeons seeking to assemble their own microsurgery training model. Methods We queried PubMed, Embase, and Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Since more affordable alternatives to high-quality microscopes and instruments such as magnifying loupes, smartphones, and tablets have become available, microsurgical training has become more accessible at home. [35][36][37][38][39][40] This seems to be especially interesting, as the study by Boecker et al suggests that implementation of regularly held in-house microsurgical training seems to reduce complication rate, operation time, and patient hospital stay. 41…”
Section: Discussionmentioning
confidence: 99%
“…Since more affordable alternatives to high-quality microscopes and instruments such as magnifying loupes, smartphones, and tablets have become available, microsurgical training has become more accessible at home. [35][36][37][38][39][40] This seems to be especially interesting, as the study by Boecker et al suggests that implementation of regularly held in-house microsurgical training seems to reduce complication rate, operation time, and patient hospital stay. 41…”
Section: Discussionmentioning
confidence: 99%
“…These models can be isolated tasks or incorporated into training curricula using cadaveric models for anastomosis practice. 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 Recent developments in microsurgical simulation and education even eliminate the use of a standard operating room microscope and instead incorporate a portable binocular microscope or monocular smartphone technology with video recording and feedback. 35 36 37 Some curricula rely on progression of skills based on learner postgraduate year (PGY), but reported outcomes are often not related to PGY level.…”
Section: Tablementioning
confidence: 99%
“…Recent developments in microsurgical simulation and education even eliminate the use of a standard operating room microscope and instead incorporate a portable binocular microscope or monocular smartphone technology with video recording and feedback. [35][36][37] Some curricula rely on progression of skills based on learner postgraduate year (PGY), but reported outcomes are often not related to PGY level. 12 The International Microsurgery Simulation Society consensus statement in 2020 emphasized the importance of nonbiologic models for instruction and need for objective assessment of trainees.…”
mentioning
confidence: 99%
“…There is some evidence to support that dry and wet laboratories have shown transferability to clinical practice, allowing progression through the learning curve without compromising patient safety [5]. Additionally, another systematic review showed that trainees could acquire skills without a microscope, using new smartphone technology with improved magnification and benchtop models [6].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 Additionally, another systematic review showed that trainees could acquire skills without a microscope, using new smartphone technology with improved magnification and benchtop models. 6…”
mentioning
confidence: 99%